Magnetic resonance for assessment of disease activity and severity in ileocolonic Crohn's disease. Issue 8 (9th January 2009) - Rimola, J; Rodriguez, S; García-Bosch, O; Ordás, I; Ayala, E; Aceituno, M; Pellisé, M; Ayuso, C; Ricart, E; Donoso, L; Panés, J
Abstract : Objective: Assessment of disease extension and activity is crucial to guide treatment in Crohn's disease. The objective of the current cross-sectional study was to determine the accuracy of MR for this assessment. Design: 50 patients with clinically active (n = 35) or inactive (n = 15) Crohn's disease underwent ileocolonoscopy (reference standard) and MR. T2-weighted and precontrast and postcontrast-enhanced T1-weighted sequences were acquired. Endoscopic activity was evaluated by CDEIS (Crohn's Disease Endoscopic Index of Severity); in addition endoscopic lesions were classified as absent, mild (inflammation without ulcers) or severe (presence of ulceration). Results: The comparison of intestinal segments with absent, mild and severe inflammation demonstrated a progressive and significant (p<0.001) increase in the following MR parameters: wall thickness, postcontrast wall signal intensity, relative contrast enhancement, presence of oedema, ulcers, pseudopolyps and lymph node enlargement. Independent predictors for CDEIS in a segment were wall thickness (p = 0.007), relative contrast enhancement (p = 0.01), presence of oedema (p = 0.02) and presence of ulcers at MR (p = 0.003). There was a significant correlation (r = 0.82, p<0.001) between the CDEIS of the segment and the MR index calculated according to the logistic regression analysis coefficients. The MR index had a high accuracy for the detection of disease activity (area under the receiver operating characteristic (ROC) curve 0.891, sensitivity 0.81, specificity 0.89) and for the detection of ulcerative lesions (area under the ROC curve 0.978, sensitivity 0.95, specificity 0.91) in the colon and terminal ileum. Conclusion: The accuracy of MR for detecting disease activity and assessing severity brings about the possibility of using MR as an alternative to endoscopy in the evaluation of ileocolonic Crohn's disease.